Financial Constraints and Nominal Price Rigidities - Almut Balleer; Nikolay Hristov; Dominik Menno (Center for Economic Studies and ifo Institute (CESifo), 2017)
This paper investigates how financial market imperfections and the frequency of price adjustment interact. Based on new firm-level evidence for Germany, we document that financially constrained firms adjust prices more often than their unconstrained counterparts, both upwards and downwards. We show that these empirical patterns are consistent with a partial equilibrium menu-cost model with a working capital constraint. We then use the model to show how the presence of financial frictions changes profits and the price distribution of firms compared to a model without financial frictions. Our results suggest that tighter financial constraints are associated with lower nominal rigidities, higher prices and lower output. Moreover, in response to aggregate shocks, aggregate price rigidity moves substantially, the response of inflation is dampened, while output reacts more in the presence of financial frictions. This means that financial frictions make the aggregate supply curve flatter for all calibrations considered in our model. We show that this differs fundamentally from models in which the extensive margin of price adjustment is absent (Rotemberg, 1982) or constant (Calvo, 1983). Hence, the interaction of financial frictions and the frequency of price adjustment potentially induces important consequences for the effectiveness of monetary policy.
Keywords: E31; E44; 330; frequency of price adjustment; financial frictions; menu cost model